Ruptured heterotopic pregnancy: a case report - Mishra, Abhishek; Gaire, Sushila; KC, Bipana; Mahat, Pradeep; Neupane, Jeevan; Chaubey, Mandip (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Heterotopic pregnancy is a rare condition when at least two pregnancies are present simultaneously at different implantation sites and only one is located in the uterine cavity. The majority of cases are diagnosed in the first trimester. Heterotopic gestation is very rare in natural conception. A high index of suspicion is required for timely diagnosis and appropriate intervention. We report a case of heterotopic pregnancy in a 26-year-old woman presented with hemoperitoneum from ruptured tubal pregnancy with live intrauterine gestation at 8 weeks of amenorrhea, diagnosed on ultrasound examination. She underwent exploratory laparotomy with right salpingectomy and post-operative period was uneventful.